Model Pembelajaran Project Based Learning (PjBL) di Pendidikan Anak Usia Dini: Systematic Literatur Review - Nur Rahmawati (Jurnal Euforia, 2026)
This study aims to analyze and synthesize previous research on the implementation of theProject Based Learning (PjBL) model in Early Childhood Education (ECE) through aSystematic Literature Review (SLR) approach. The study employed a qualitative SLR method(meta-synthesis) by reviewing articles retrieved from Google Scholar published between2022 and 2026. The analysis followed seven systematic stages: literature searching,literature screening, study selection, literature mapping, quality assessment, findingssynthesis, and conclusion drawing. The findings indicate that Project Based Learning is achild-centered, contextual, collaborative, and experiential learning model that promotesmeaningful learning experiences. The implementation of PjBL has been shown to positivelyinfluence children's creativity, critical thinking, problem-solving skills, collaboration,communication, as well as cognitive and socio-emotional development. The successfulimplementation of PjBL is influenced by teachers' competencies, the availability of learningfacilities and instructional media, parental involvement, and a supportive learningenvironment. This study recommends strengthening teachers' professional competencies,providing adequate learning resources, and fostering collaboration between schools andparents to optimize the implementation of PjBL. The findings are expected to serve as avaluable reference for educators, practitioners, and researchers in developing innovativeproject-based learning practices that are aligned with the developmental characteristics ofyoung children.